Imaginando o Asilo - Gomides , Adeuza Pereira; Bernhardt, Cristiane Otilia Colossi; Minotti , Fabielle Ferreira da Silva; Reis , Geissyane Aparecida Oliveira dos (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf